Analisis Pembiayaan Modal Kerja Terhadap Pertumbuhan Usaha Nasabah PT. Fifgroup Muara Sabak: Penelitian - Okrice Andha Fia; M. Arif Musthofa; Erwina Kartika Devi (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Modern economy places capital as a strategic element in driving business growth, especially for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the effect of working capital financing on the business development of customers of PT Federal International Finance (FIFGROUP) Muara Sabak Branch in Tanjung Jabung Timur Regency. The approach used is quantitative with a simple linear regression method. A sample of 100 respondents was selected using cluster sampling techniques from a population of 134 customers. The research instrument has been tested for validity and reliability, and data processing was carried out using SPSS version 16.0. The results of the study indicate that working capital financing has a positive and significant effect on business development (tcount = 4.193; sig. = 0.000), with a regression equation of Y = 13.193 + 0.301X. However, its contribution to the variation in business development is only 15.2% (R² = 0.152), indicating that there are other factors outside of financing that play a role. These findings suggest the importance of integrating financing with training, business mentoring, and market access to encourage sustainable MSME growth